Human aspects of IT for the aged population : first International Conference, ITAP 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015. Proceedings /: first International Conference, ITAP 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015. Proceedings. Design for aging : Part I (2015) - Unknown
No abstract available